Symptoms and Physiological Responses to Prolonged, Repeated, Low‐Level Tooth Clenching in Humans. Issue 3 (7th March 2015) - Takeuchi, Tamiyo; Arima, Taro; Ernberg, Malin; Yamaguchi, Taihiko; Ohata, Noboru; Svensson, Peter
<x xml:space="preserve">Abstract</x> Background The traditional view contends bruxism, such as tooth grinding/clenching, is part of the etiology of temporomandibular disorders (TMD) including some subtypes of headaches. The purpose of this study is to investigate if a low‐level but long‐lasting tooth‐clenching task initiates TMD symptoms/signs. Methods Eighteen healthy participants (mean age ± SD, 24.0 ± 4.3 years) performed and repeated an experimental 2‐hour tooth‐clenching task at 10% maximal voluntary occlusal bite force at incisors (11.1 ± 4.6 N) for three consecutive days (Days 1‐3). Pain and cardiovascular parameters were estimated during the experiment. Results The task evoked pain in the masseter/temporalis muscles and temporomandibular joint after 40.0 ± 18.0 minutes with a peak intensity of 1.6 ± 0.4 on 0‐10 numerical rating scale (NRS) after 105.0 ± 5.0 minutes (Day 1). On Day 2 and Day 3, pain had disappeared but the tasks, again, evoked pain with similar intensities. The onset and peak levels of pain were not different between the experimental days (P = .977). However, the area under the curve of pain NRS in the masseter on Day 2 and Day 3 were smaller than that on Day 1 (P = .006). Cardiovascular parameters changed during the task but not during the days. Conclusions Prolonged, low‐level tooth clenching evoked short‐lived pain like TMD. This intervention study proposes that tooth clenching alone is insufficient to initiate longer lasting and self‐perpetuating symptoms of TMD, which may require other risk factors.